Biofilm dysbiosis and caries activity: a surface or an individual issue? - Laís Daniela EV; Joice Faria POLONI; Nailê DAMÉ-TEIXEIRA; Rodrigo Alex ARTHUR; Daniela Jorge CORRALO; Sandra Liana HENZ; Thuy DO; Marisa MALTZ; Clarissa Cavalcanti Fatturi PAROLO (University of São Paulo, 2023)
Abstract Objective This study aimed to analyze the functional profile of supragingival biofilm from sound (CAs), active (CAa), and inactive (CAi) enamel caries lesions from caries-active individuals to provide insights into the diversity of biological processes regarding biofilm dysbiosis. Methodology A metatranscriptome analysis was performed in biofilm samples collected from five caries-active individuals. Total RNA was extracted, and the microbial cDNAs were obtained and sequenced (Illumina HiSeq3000). Trimmed data were submitted to the SqueezeMeta pipeline in the co-assembly mode for functional analysis and further differential gene expression analysis (DESeq2). Results Bioinformatics analysis of mRNAs revealed a similar functional profile related to all analyzed conditions (CAa, CAi, and CAs). However, active and inactive surfaces share up-regulated genes (gtsA; qrtT; tqsA; pimB; EPHX1) related to virulence traits that were not overrepresented in sound surfaces. From a functional perspective, what matters most is the individual carious status rather than the surface condition. Therefore, pooling samples from various sites can be carried out using naturally developed oral biofilms but should preferably include carious surfaces. Conclusion Metatranscriptome data from subjects with caries activity have shown that biofilms from sound, arrested, and active lesions are similar in composition and function.